Nardosinone Enhances Nerve Growth Factor-Induced Neurite Outgrowth in a Mitogen-Activated Protein Kinase- and Protein Kinase C-Dependent Manner in PC12D Cells - Ping Li; Tohru Yamakuni; Kimihiro Matsunaga; Shunzo Kondo; Yasushi Ohizumi (Elsevier, 2003)
ABSTRACT: The mechanism to enhance nerve growth factor (NGF, 2 ng/ml)-induced neurite outgrowth from PC12D cells by nardosinone isolated from Nardostachys chinensis was examined. It was shown that the potentiation of the NGF-induced neurite outgrowth by nardosinone was mitogen-activated protein (MAP) kinase-dependent, but was not accompanied by stimulation of NGF-induced increase in MAP kinase phosphorylation. Furthermore, this augmentation of NGF-induced neurite outgrowth was abolished by GF109203X, a protein kinase C (PKC) inhibitor. These results suggest that the enhancement of NGF-induced neurite outgrowth from PC12D cells by nardosinone involves activation of a down-stream step of the MAP kinase-dependent cascade of NGF coupled with PKC.